Origin of Earth’s Magnetic Field, its Nature and Behavior, Geophysical Consequences, and Danger to Humanity: A Logical Progression of Discoveries Review - Herndon, J. Marvin (European Journal of Applied Sciences, 2022)
Albert Einstein was unsuccessful in attempting to understand the origin of Earth’s magnetic field, which he considered to be one of the five most important unsolved problems in physics. Many who followed Einstein failed to understand the origin of the geomagnetic field because crucial prerequisite information was not available or was being systematically ignored by the geoscience community. Here I review the logical progression of discoveries from Earth’s protoplanetary origin that led to my concept of a nuclear fission ‘georeactor’ at Earth’s center, evidence of its existence, and the mechanism for generally maintaining stable operation over geological time scales and producing Earth’s magnetic field. In the micro-gravity environment at Earth’s center, uranium, mixed with reactor poisons from fission and decay products, forms the georeactor sub-shell, which is kept in motion by nuclear fission energy from uranium that settles-out forming the georeactor sub-core. The amount of nuclear fission energy produced in the sub-core reaches a steady state wherein the amount of fission energy produced balances the uranium precipitation and the energy transferred to the inner core heat-sink by convection. Sub-shell convection twisted by planetary rotation, I posited, produces the Earth’s magnetic field by the dynamo concept first espoused by Elsasser. Occasionally, sub-shell convection is disrupted, for example, by surface trauma such as from a great meteor impact or by an intense outburst of charged particles from the sun, which can lead to a geomagnetic reversal or excursion. Such convection disruption may lead to an extra burst of nuclear fission energy which, by replacing the lost heat of protoplanetary compression energy, can trigger earthquakes and volcanic activity at Earth’s surface. Eventually, the geomagnetic field will collapse with potentially devastating consequences for our highly-integrated, technology-based infrastructure. Humanity should approach that unknown time with eyes open and with a willingness to work together for common survival.